2019
DOI: 10.3390/f10040338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lime Application and Understory Removal on Soil Microbial Communities in Subtropical Eucalyptus L’Hér. Plantations

Abstract: Soil microorganisms play key roles in ecosystems and respond quickly to environmental changes. Liming and/or understory removal are important forest management practices and have been widely applied to planted forests in humid subtropical and tropical regions of the world. However, few studies have explored the impacts of lime application, understory removal, and their interactive effects on soil microbial communities. We conducted a lime application experiment combined with understory removal in a subtropical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…This result is in line with most previous studies conducted in temperate and subtropical plantations (e.g., Wan et al, 2019;Winsome et al, 2017), confirming the strong controls of understory plants on soil microbial communities (Yin et al, 2016). In general, most fungi are moderately acidophilic; therefore, fungal activities would be facilitated and the microbial communities would typically shift from bacterial to fungal as soil pH decreases (Wan et al, 2019;Zhao et al, 2015). The negative relationship between 18:2ω6,9c and soil pH in this study implied that the altered soil microbial community would be partly resulted from the decreased soil pH (Figures 2 and 4).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is in line with most previous studies conducted in temperate and subtropical plantations (e.g., Wan et al, 2019;Winsome et al, 2017), confirming the strong controls of understory plants on soil microbial communities (Yin et al, 2016). In general, most fungi are moderately acidophilic; therefore, fungal activities would be facilitated and the microbial communities would typically shift from bacterial to fungal as soil pH decreases (Wan et al, 2019;Zhao et al, 2015). The negative relationship between 18:2ω6,9c and soil pH in this study implied that the altered soil microbial community would be partly resulted from the decreased soil pH (Figures 2 and 4).…”
Section: Discussionsupporting
confidence: 93%
“…In most forest plantations, understory removal (UR) is a common management practice to reduce competition for resources and increase stand productivity (Giuggiola et al, 2018;Qiao, Miao, Silva, & Horwath, 2014;Zhao et al, 2013). Previous studies have observed that UR caused substantial changes in soil microclimate, nutrient availability, and microbial composition and structure (Wan et al, 2014(Wan et al, , 2019. Accordingly, UR could potentially influence litter decomposition and P release through its effects on microclimate, soil microorganisms, and soil nutrient availability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The land group was enriched in signal transduction mechanisms (T), cell cycle control, cell division, chromosome partitioning (D) among the COG categories (Figure 5B). It has been suggested that land bacteria might respond quickly to environmental variation (Wan et al, 2019). At the same time, it has also been suggested that having dispensable genes involved in cell wall biogenesis, transport and metabolism of amino acids, carbohydrates, inorganic ions, and secondary metabolites, could be how certain members of Azospirillum adapt to terrestrial niches (Wisniewski-Dyé et al, 2011).…”
Section: The Pan-genome Of the Bp Bacteriamentioning
confidence: 99%
“…Furthermore, both lime application and understory removal significantly reduce the litter decomposition rates, which may impact the microbe-mediated soil ecological process. They suggest that lime applications may not be suitable for the management of subtropical Eucalyptus plantations [24]. Wu, Li, Chen et al examine the effects of two native phosphate solubilizing bacteria (PSB), and a mixture of both strains on the growth of seedlings of Camellia oleifera (Theaceae).…”
Section: Theme 4: Interactions Of Woody Plants Within a Changing Envimentioning
confidence: 99%